Kompensasi dan Keuntungan SDM Sebagai Bentuk Motivasi Kerja Karyawan Bidang Pendidikan - Muhammad Abrori (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this paper is to present the management of compensation and its benefits for an educational institution in increasing employee motivation. Nowadays, with the increasing level of competition in the quality of education, every institution faces the challenge of keeping up with the challenges of the times. Therefore, an institution or educational institution must be competitive, and one of the tools that institutions can use is compensation. If employees believe that the compensation scheme is fair and competitive, then the institution will find it easier to attract prospective employees, retain them, and motivate them to further improve performance, thus increasing productivity and enabling an educational institution to produce competitive products or outputs. In the end, an educational institution not only stands out from the competition, but is also able to maintain its prestige, even increase profitability and develop its quality. The results show that compensation as a form of employee work motivation in senior high schools is carried out by analyzing and identifying the purpose of compensation, factors that affect compensation, and the relationship between compensation and employee work motivation.